Le temps de l'appropriation d'une classe mobile par les enseignants à l'école primaire - Sandra Nogry; Carine Sort (Centre National d'Enseignement à Distance, 2016)
In France, the number of deployments in digital equipment at primary school including mobile classes composed of laptops or digital tablets is drastically increasing. The appropriation of these devices in situation needs to be investigates. This research consists in a diachronic analysis of teachers' activity in order to highlight the different temporality that plays a role in the appropriation process. To this end, a study was conducted in an elementary school in Seine Saint-Denis during two and a half years. Ownership is a non-linear process that follows the time. The activity analysis highlights two different trajectories of appropriation. The first path involves a series of explorations consisting in using the laptops in classroom in many disciplines. During these explorations potentials and new constraints gradually emerge. In the process, the time constraints are increasingly important. The second path is the establishment of a practice based on existing habits; this practice is very stable throughout the duration of the project. During the process, a gap between the change of the concerns of the teacher and transformation of his practice is observed. The time constraints emerging during the process of appropriation is subject to a more systematic discussion.